European venture toolbox : the path for SMEs to grasp and defend opportunities - Kirk, Nicholas H.; Zollo, Lamberto (Emerald Publishing Limited, 2021)
Not all markets are alike: the European entrepreneur requires knowledge on how to avoid pitfalls before believing and focusing on opportunity. European Venture Toolbox features the leadership toolkit future decision makers, innovators, and entrepreneurs need to build a venture in Europe. Many European entrepreneurs are prone to the rhetoric of company building based on fast-growing start-up survivors, abundance of circulating capital, and sub-optimal business models monetizing late. They fall into the trap of thinking a mildly successful company can survive in the European ecosystem even if it does not thrive. This toolbox provides a framework to assess risk and return of choices, iteratively implement business, and avoid being blinded by incorrect principles not grounded in financial reality. European Venture Toolbox: The path for SMEs to grasp and defend opportunities is a compelling book for all small-to-medium enterprises. Written by a theoretician and a practitioner, it captures Europe-specific perspectives, examples, and case studies to provide an alternative insight. The Entrepreneurial Behaviour series is focused on expanding the scope of Entrepreneurial Behaviour theory and analysis and enriching practice by encouraging multi-cultural and multi-disciplinary approaches.
Keywords: Entrepreneurship -- Europe.; Small business -- Europe -- Management.; Small business -- Europe -- Decision making.; Risk management -- Europe.; Business & Economics -- Entrepreneurship.; Management & management techniques.; elektronické knihy; electronic books